Novel anaerobic membrane bioreactor (AnMBR) design for wastewater treatment at long HRT and high solid concentration. (February 2018) - Berkessa, Yifru Waktole; Yan, Binghua; Li, Tengfei; Tan, Ming; She, Zonglian; Jegatheesan, Veeriah; Jiang, Heqing; Zhang, Yang
Graphical abstract: Highlights: Placement of membrane unit above three phase separator mitigated fouling tendency. High permeate flux and low filtration resistance was achieved. High COD removal, effluent with SUVA < 1.00 was achieved. Microbial mechanism of reduced membrane fouling was interpreted. Abstract: Performance of two novel designed anaerobic membrane bioreactor (AnMBRs) for wastewater treatment at long hydraulic retention time (HRT, 47 days) and high sludge concentration (22 g·L −1 ) was investigated. Results showed steady chemical oxygen demand (COD) removal (>98%) and mean biogas generation of 0.29 LCH4 ·g −1 COD. Average permeates flux of 58.70 L·m −2 ·h −1 and 54.00 L·m −2 ·h −1 were achieved for reactors A and B, respectively. On top of reactor configuration, long HRT caused biofilm reduction by heterotrophic bacteria Chloroflexi resulting in high membrane flux. Mean total membrane resistances (2.23 × 10 9  m −1 ) and fouling rates (4.00 × 10 8  m −1 ·day −1 ) of both reactors were low suggesting better membrane fouling control ability of both AnMBRs. Effluent quality analysis showed the effluent soluble microbial products (SMP) were dominated by proteins compared to carbohydrates, and specific ultraviolet absorbance (SUVA) analysis revealed effluent from both reactors had low aromaticity with SUVA < 1 (L·mg −1 ·m −1 ) except for the first ten days.